2021
DOI: 10.1093/plphys/kiab146
|View full text |Cite|
|
Sign up to set email alerts
|

A tobacco ringspot virus-based vector system for gene and microRNA function studies in cucurbits

Abstract: Cucurbits are economically important crops worldwide. The genomic data of many cucurbits are now available. However, functional analyses of cucurbit genes and non-coding RNAs have been impeded because genetic transformation is difficult for many cucurbitaceous plants. Here, we developed a set of tobacco ringspot virus (TRSV)-based vectors for gene and microRNA (miRNA) function studies in cucurbits. A TRSV-based expression vector could simultaneously express GREEN FLUORESCENT PROTEIN (GFP) and heterologous vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…To circumvent this obstacle, we decided to investigate the molecular mechanisms controlling CGMMV infection in watermelon fruits through reverse genetics using a CGMMV‐based virus‐induced gene silencing (VIGS) pV190 vector as described previously (Lange et al, 2013 ; Liu et al, 2020 ). Currently, two VIGS vectors (i.e., the CGMMV‐based pV190 vector and a tobacco rattle virus [TRV]‐based vector) have been reported to be effective in gene silencing in cucurbits (Fang et al, 2021 ; Liu et al, 2020 ). In this study, we found that the pV190 vector‐induced gene silencing in watermelon fruits lasted more than 54 days and thus is suitable for studies of CGMMV infection in watermelon fruits and possibly other cucurbit crops.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this obstacle, we decided to investigate the molecular mechanisms controlling CGMMV infection in watermelon fruits through reverse genetics using a CGMMV‐based virus‐induced gene silencing (VIGS) pV190 vector as described previously (Lange et al, 2013 ; Liu et al, 2020 ). Currently, two VIGS vectors (i.e., the CGMMV‐based pV190 vector and a tobacco rattle virus [TRV]‐based vector) have been reported to be effective in gene silencing in cucurbits (Fang et al, 2021 ; Liu et al, 2020 ). In this study, we found that the pV190 vector‐induced gene silencing in watermelon fruits lasted more than 54 days and thus is suitable for studies of CGMMV infection in watermelon fruits and possibly other cucurbit crops.…”
Section: Introductionmentioning
confidence: 99%
“…To further elucidate the functions of CsChi23 and CsHB15 in Foc resistance, gene expression was knocked down in 3461 plants through a VIGS system (Fang et al ., 2021; Dong et al ., 2022). To test the suitability of the VIGS system, we conducted initial experiments using a pTRSV2 :: CsPDS construct.…”
Section: Resultsmentioning
confidence: 99%
“…For tobacco ringspot virus (TRSV)‐based VIGS experiments, we used an injection method for cucurbits (Fang et al ., 2021; Dong et al ., 2022). Briefly, the gene‐specific fragments for CsChi23 and CsHB15 were inserted into pTRSV2 vector and transformed into A. tumefaciens GV3101.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, TRV has been used to determine the functions of genes associated with GT formation and development (Janga et al, 2019;Zang et al, 2021). TRV1 and TRV2 are one set of the most widely used vectors (Ratcliff et al, 2001) that have been used to silence genes in Nicotiana benthamiana, tomato, petunia, Arabidopsis, cotton, and cucumber (Liu et al, 2004;Fu et al, 2005;Fang et al, 2021). The PDS gene is a wellknown reporter used in the VIGS system, and PDS-silenced plants exhibit the photobleaching phenotypes (Liu and Page, 2008).…”
Section: Analysis Of Gene Function Using Vigsmentioning
confidence: 99%